Vascular hamartoma in the distal region of the anterior face of the left forearm, a rare lesion: a case report - Serrano, Erik B.; Serrano, Beatriz R.; Vázquez, Lucero G. S.; Arias, Francisco de J. C.; Campa, Kassandra J. E. (International Journal of Research in Medical Sciences, 2023)
The word hamartoma is derived from the Greek word hamartia meaning "to err" or "to blame", with the addition of "-oma" denoting a tumor-like growth. Hamartomas are non-malignant tissue malformations characterized by defective dissemination of fully differentiated cells and soft tissue native to the affected organ. If the tissues involved are composed of blood vessels, they are called vascular hamartomas. In our manuscript we describe the case of a 16-year-old adolescent with the presence of a tumor in the distal region, anterior face of the left forearm, who underwent an excisional biopsy with histopathological report of vascular hamartoma, currently with adequate postoperative evolution. The most commonly reported site of occurrence of vascular hamartomas is on the face and they are generally asymptomatic and silent at different stages of life. The definitive diagnosis for this type of pathology is by histopathology. Vascular hamartomas are a rarely reported benign pathology, due to their low incidence, this can make timely diagnosis difficult, as well as the ideal treatment for these patients.